A new putative natural hybrid of Cyrtopodium (Orchidaceae) from the south coast of Brazil - Batista, João A. N.; Medeiros, Alexandre Da Silva (Phytotaxa, 2022)
A new putative natural hybrid of Cyrtopodium, C. × flavopunctatum, from sandy coastal plain vegetation, known as restinga, in the state of Santa Catarina in southern Brazil is described and illustrated. It was found growing among a population of C. flavum and is similar to that species in vegetative and overall floral morphology, but distinguished by the sepals and petals with brown spots, lateral lobes of lip and base of the central lobe orange or orange-spotted, very short isthmus (1–2 mm long), lip midlobe margins slightly verrucose and flowers slightly citrusy-scented. In the color of the flowers, it is intermediate between C. flavum, with completely yellow flowers, and C. gigas or C. palmifrons, epiphytic species with profusely dotted flowers that occur in the same region and bloom at the same time as C. flavum. Additional studies with genetic data are needed to confirm the possible hybrid origin and the identity of the second parental species.